Effectiveness of DVD vs. group-initiated diabetes prevention on information uptake for high & low health literacy participants. Issue 5 (May 2019) - Goessl, Cody; Estabrooks, Paul; You, Wen; Britigan, Denise; DeAlba, Armando; Almeida, Fabio
Highlights: Research is scant on the differences in information uptake by varied modalities. Teach-to-goal strategies may enhance understanding of educational objectives. Health literacy strategies may be needed to improve patient engagement. Patient Education Abstract: Objective: This study evaluates the effectiveness of technology versus in-person, group-initiated diabetes prevention to enhance comprehension of learning objectives between patients with differing health literacy (HL). Methods: Evidence-based content through either a DVD (n = 217) or in-person, group class (n = 225) to initiate the intervention. A teach-back call was used to assess comprehension of, and reinforce, learning objectives. Chi-squared was used to determine differences between conditions (DVD vs Class) and HL levels (High n = 361 vs. Low n = 81) and regression analyses were used to examine relationships. Results: DVD participants performed significantly better across teach back questions (15.4 ± 2.5 v. 14.8 ± 2.6, p < 0.01), demonstrated comprehension in fewer teach-back rounds (1.9 ± 0.7 v. 2.1 ± 0.7, p < 0.01), and answered more questions correctly on the first try (4.2 ± 1.6 v. 3.4 ± 1.8, p < 0.01). Models for HL levels and modality by HL level were statistically significant (p < 0.01) favoring the DVD. Conclusion: Initiating a diabetes prevention program with the use of a DVD appears to be a superior option to in-person, class sessions. Teach-back and teach-to-goal strategies enables participants of both high and low health literacy levels to receive and confirm mastery of diabetes prevention objectives. Practice Implications: A teach-back call may improve information uptake increasing the likelihood of health behavior uptake.